Pengaruh Brand Image dan Social Media Marketing Terhadap Keputusan Pembelian Konsumen Satuone Coffee and Roastery - Fauzi, M. Fachri; Utama, Amrin Mulia; Syahputri, Yuni (Economics, Business and Management Science Journal, 2025)
Coffee and Roastery Trend. In addition, consumer lifestyle about coffee is also a factor causing the increase in coffee shop trends. With the many coffee shops in Binjai City with various concepts, it is a challenge for Satuan Coffee and Roastery to compete in offering their products at different prices according to the needs of their customers and marketers need to have a superior marketing strategy. The objectives of this study are: To find out whether Brand Image has a positive effect on Satuone Coffee and Roastery. To find out whether Social Media Marketing has a positive effect on Satuone Coffee and Roastery. To find out whether Brand Image and Social Media Marketing have a positive effect simultaneously on purchasing decisions at Satuone Coffee and Roastery. In this study, the author uses quantitative research by using descriptive analysis on each variable and further analyzed in data analysis. This study consists of two variables, namely the independent variable and the dependent variable. The results of the study showed that the Brand Image variable obtained a tcount value ttable (12.348 2.0) so it can be concluded that Brand Image influences consumer purchasing decisions at Satuone Coffee and Roastery. The Social Media Marketing variable obtained a tcount value ttable (2.216 2.0) so it can be concluded that Social Media Marketing influences consumer purchasing decisions at Satuone Coffee and Roastery. The taste variable for purchasing decisions obtained a tcount value ttable (3.931 2.0) so it can be concluded that Brand Image and Social Media Marketing partially influence consumer purchasing decisions at Satuone Coffee and Roastery.